Effective dissociation temperature for estimation of electric arc plasma composition - Babich, I.L.; Boretskij, V.F.; Veklich, A.N. (Вопросы атомной науки и техники, 2011)
Spectroscopy investigations of the thermal multicomponent plasma of the electric arc discharge between copper
electrodes in carbon dioxide flow were carried out. The technique of calculation of plasma equilibrium composition is
discussed. The influence of thermal dissociation of molecular gas on the plasma state is estimated. It was assumed that
the thermal dissociation of molecules of working gas play the key role in deviation from local thermodynamic
equilibrium (LTE) in plasma. Спектроскопічними методами досліджено термічну багатокомпонентну плазму електродугового розряду
між мідними електродами у потоці вуглекислого газу. Обговорюється методика розрахунку рівноважного
складу плазми. Оцінено вплив термічної дисоціації молекулярного газу на стан плазми. Припускається, що
термічна дисоціація молекул робочого газу є основним механізмом відхилення від локальної термодинамічної
рівноваги в плазмі. Спектроскопическими методами исследована термическая многокомпонентная плазма электродугового
разряда между медными электродами в потоке углекислого газа. Обсуждается методика расчета равновесного
состава плазмы. Оценено влияние термической диссоциации молекулярного газа на состояние плазмы.
Предполагается, что термическая диссоциация молекул рабочего газа является основным механизмом
отклонения от локального термодинамического равновесия в плазме.